2011
DOI: 10.1124/dmd.110.037259
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9-Mediated Metabolic Activation of Losartan Detected by a Highly Sensitive Cell-Based Screening Assay

Abstract: ABSTRACT:Drug-induced hepatotoxicity is a major problem in drug development, and reactive metabolites generated by cytochrome P450s are suggested to be one of the causes. CYP2C9 is one of the major enzymes in hepatic drug metabolism. In the present study, we developed a highly sensitive cell-based screening system for CYP2C9-mediated metabolic activation using an adenovirus vector expressing CYP2C9 (AdCYP2C9). Human hepatocarcinoma HepG2 cells infected with our constructed AdCYP2C9 for 2 days at multiplicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Recombinant adenoviruses expressing CYP3A4 (AdCYP3A4), CYP2C9 (AdCYP2C9), and green fluorescent protein (AdGFP) were constructed as in our previous studies (Hosomi et al, 2010;Iwamura et al, 2011). Recombinant adenoviruses expressing PGRMC1 (AdPGRMC1) and CYP2E1 (AdCYP2E1) were created as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant adenoviruses expressing CYP3A4 (AdCYP3A4), CYP2C9 (AdCYP2C9), and green fluorescent protein (AdGFP) were constructed as in our previous studies (Hosomi et al, 2010;Iwamura et al, 2011). Recombinant adenoviruses expressing PGRMC1 (AdPGRMC1) and CYP2E1 (AdCYP2E1) were created as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Glimepiride is a sulfonylurea derivative and is metabolized by cytochrome P-450 (CYP2C9). Losartan is a substrate of CYP2C9, which is metabolized by CYP3A4 [Iwamura et al 2011;Yasar et al 2001]. Therefore, it is hypothesized that losartan may influence the pharmacological activity of glimepiride by any one of the above mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Iwamura et al (2011) reported that HepG2 cells infected with adenovirus vector expressing CYP2C9 significantly increase the cytotoxicity of BBR. McDonald and Rettie (2007) suggested that the catechol metabolite 5,6-dihydroxybenzbromarone, which is formed via 6-OH-BBR, and its o-quinone form may be reactive metabolites and that the sequential metabolism is catalyzed by CYP2C9, although they did not show the formation of such reactive metabolites directly from BBR in liver microsomal systems, and their cytotoxicity has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that human hepatocarcinoma HepG2 cells infected with adenovirus vector expressing CYP2C9 significantly increase the cytotoxicity of BBR, suggesting that CYP2C9 is associated with BBR-induced cytotoxicity (Iwamura et al, 2011). Thus, the formation of 6-OH-BBR catalyzed by CYP2C9 was thought to play a key role in hepatic toxicity.…”
Section: Introductionmentioning
confidence: 99%